‘연줄’인가, ‘연결’인가?: 인적 네트워크의 노동시장 효과 분석 - 김영철 (12608, 2012)
This paper analyzes the effectiveness of social networks in finding jobs and estimates the value of job search network using the Korean Laber and Income Panel Study (KLIPS) dataset and utilizing the Difference-in-Difference Propensity Score Matching (PSM)